LEGAL PROTECTION FOR SUBSIDIARY DIRECTORS IN CORPORATE ENVIRONMENTAL CRIMES - Pamungkas Ridaningjati; Bhisma Dewanata; Daniel Giovanni Pandapotan L. Tobing; Gusti Muhammad Reyhan Farisi; Nizar Naren Danu (Fakultas Hukum Universitas Udayana, 2026)
A Limited Liability Company manages its affairs through corporate organs, with the board of directors serving as the central controlling body. As both individuals (natuurlijk persoon) and representatives of the legal entity (rechtspersoon), directors carry a dual layer of responsibility under Article 98 of the Indonesian Company Law. In environmental law, the Environmental Protection and Management Act establishes that environmental crimes may be committed by, for, or on behalf of a corporation, thus extending criminal liability to both the corporate entity and individuals who order or direct such crimes. Liability becomes more complex within a holding company structure, where the parent company’s influence can significantly undermine the independence of subsidiary directors. This research explores the binding effect of parent company policies on subsidiaries and the limits of directors’ liability in environmental corporate crimes. The findings demonstrate that parent company policies frequently dominate subsidiary operations due to economic interdependence in corporate groups. Subsidiary directors acting in line with the Articles of Association and parent company policies may be shielded from personal liability under the Business Judgment Rule (BJR). Nonetheless, liability may still arise when directors knowingly tolerate or permit conduct that is manifestly unlawful or contrary to moral principles.